Comparative analysis of frameworks for mobile application development: native, hybrid or cross-platform solutions - A. B. Temirova (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The purpose of this study is to conduct a comparative analysis of various frameworks for the development of mobile applications: native, hybrid and cross-platform solutions.Method. To achieve this goal, methods of analysis, synthesis and comparison were used. The characteristics of various mobile application development frameworks were analyzed, including their performance, cost, and access to device capabilities.Result. Native frameworks have been found to have the highest performance and the ability to provide the most native look and functionality for an application. This approach has limitations as it requires separate development for each platform, which leads to increased time and resource costs. Hybrid solutions have proven to be cost-effective, allowing you to use a single code base to create applications for different platforms. This simplifies the development and maintenance process. Hybrid apps may have limited performance due to the use of WebView to display the interface and limited access to device capabilities. Cross-platform frameworks, on the other hand, provide a balance between performance and resource efficiency. They allow you to use a single code base to create applications for multiple platforms and can achieve satisfactory performance. However, they may have limited access to certain device capabilities and the appearance of applications.Conclusion. The results make a new contribution to the field by providing a detailed analysis of mobile app development approaches and frameworks used to build them. The results can be used to make informed decisions regarding the choice of framework for mobile app development.